Analysis of the optical and thermal properties of transparent insulating materials containing gas bubbles. (5th May 2016) - Cai, Qilin; Ye, Hong; Lin, Qizhao
Highlights: Transparent insulating medium containing gas bubbles was proposed. Radiative transfer and thermal conduction models were constructed. Bulk transmittance increases first and then decreases with the bubble number. Effective thermal conductivity decreases with increasing filling ratio. High filling ratio with large bubbles is preferred for good performance. Abstract: As a medium of low absorption and low thermal conduction, introducing gas bubbles into semitransparent mediums, such as glass and polycarbonate (PC), may simultaneously improve their light transmission and thermal insulation performances. However, gas bubbles can also enhance light scattering, which is in competition with the effect of the absorption decrease. Moreover, the balance between the visible light transmittance and the effective thermal conductivity should also be considered in the material design. Therefore, a radiative transfer model and the Maxwell–Eucken model for such material were employed to analyze the optical and thermal performances, respectively. The results demonstrate that the transmittance increases when the bubble radius ( r ) increases with a fixed volume fraction of the gas bubbles ( f v ) due to the increased scattering intensity. In addition, the effective thermal conductivity always decreases with increasing f v . Thus, to achieve both good optical and thermal performances, high f v with large r is preferred. When f v = 0.5, the transmittance can be kept larger than 50% as long as r ≥ 0.7 mm. To elucidate the application performance, the heat transfer of a freezer adopting the glass or PC with gas bubbles as a cover was analyzed and the energy saving can be nearly 10%.